Vegetation biomass and habitat selection by a newly introduced population of muskoxen in northern Quebec - Nault, René; Mathieu, Carole; Crête, Michel (Rangifer, 1993)
Ground coverage by woody and herbaceous plant species and standing biomass of vegetation susceptible to being grazed upon were estimated in a 156 km2 area where 190 muskoxen were censused during the preceding autumn. Habitat use was estimated with droppings census. Six terrestrial habitat types were delineated on 1:32 000 aerial photographs and randomly sampled: low shrub on xeric sites (LSX; 64 km2), low shrub on mesic sites (LSM; 45 km2), bare ground (BG; 27 km2), forest-tundra (FT; 12 km2), wet meadow (WM; 2 km2) and riparian willows (RW; 1 km2). Dominant plant species varied greatly between habitat types, and only a few such as Betula glandulosa, Salix arctophila, and Polygonum viviparum were common. Tall shrubs were present only in RW where they covered most of the ground, and in FT. Low shrubs were uniformly distributed and covered 18-32% of the ground, with the exception of RW (5%). Ground cover by herbs had a similar range (i.e. 20-37%), except in RW where the mean exceeded 50%. Mosses and lichens occupied about half of the ground everywhere. Phytomass exhibited great variation within and between habitat types; extreme values averaged 892 kg*ha-1 in LSX, and 1965 kg*ha-1 in LSM. However the difference was not significant due to limited sample size and within habitat variance. Nevertheless the mass of herbaceous dicots was greater in RW than in any other habitat type. Total phytomass was 2-20 times greater in northern Québec than in Greenland. Based on droppings density, muskoxen preferred RW over BG and FT, and LSX over BG. Although the density of muskoxen in the study area was high relative to other muskox ranges, habitat quality and quantity should allow continued population growth.